2003
DOI: 10.1128/jcm.41.3.1109-1113.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Gentamicin-Resistant Enterococci in the United States: Evidence of Spread from Animals to Humans through Food

Abstract: We evaluated the molecular mechanism for resistance of 360 enterococci for which the gentamicin MICs were >128 g/ml. The aac(6)-Ie-aph(2؆)-Ia, aph(2؆)-Ic, and aph(2؆)-Id genes were identified by PCR in isolates from animals, food, and humans. The aph(2؆)-Ib gene was not identified in any of the isolates. Two Enterococcus faecalis isolates (MICs > 1,024 g/ml) from animals failed to generate a PCR product for any of the genes tested and likely contain a new unidentified aminoglycoside resistance gene. Pulsed-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
87
1
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 31 publications
7
87
1
8
Order By: Relevance
“…Furthermore, our results showed that the most predominant PFGE pattern among E. coli and enterococci strains from animals in each farm was not found. These findings are similar to those of other researchers (Aarestrup, 2000;Donabedian et al, 2003;Hoyle et al, 2006;Liebana et al, 2003;Manson et al, 2004). The demonstration of diversity in the PFGE patterns on the species level will be essential for understanding the molecular ecology of E. coli and enterococci in the intestine of animals and humans.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, our results showed that the most predominant PFGE pattern among E. coli and enterococci strains from animals in each farm was not found. These findings are similar to those of other researchers (Aarestrup, 2000;Donabedian et al, 2003;Hoyle et al, 2006;Liebana et al, 2003;Manson et al, 2004). The demonstration of diversity in the PFGE patterns on the species level will be essential for understanding the molecular ecology of E. coli and enterococci in the intestine of animals and humans.…”
Section: Discussionsupporting
confidence: 80%
“…It is not known if the new bacterial species identified in the present study plays a role in the pathogenesis of infections or in the transmission of antimicrobial resistance and food contamination, as it has been described for the enterococci (Donabedian et al, 2003). Although specific clinical manifestations in humans for V. fluvialis have yet to be confirmed, it has been identified from the following human clinical sources: peritoneal fluid, bite wounds, blood and cerebrospinal fluid (Teixeira et al, 1997).…”
mentioning
confidence: 91%
“…Across the globe, a variety of antimicrobial agents are available for therapeutic use in animals. Many studies have supported the claim that with the increased use of antimicrobial agents in animals and humans, an increased prevalence of resistant strains has emerged as a direct consequence of the antimicrobial use (Donabedian et al, 2003;Hershberger et al, 2005). Infections by vancomycin-resistant enterococci (VRE) through the food chain from animals to humans have been documented in Europe (Wegener et al, 1999), and VREs have been detected and isolated in many parts of world.…”
Section: Introductionmentioning
confidence: 99%